Implications of Illocutionary Speech Acts Study in Language Learning for Foreigners - Mayrita, Hastari; Andriani, Margareta; Fransiska, Erika Jun (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This study aims to explore the types and functions of speech acts in BIPA (Indonesian Language for Foreign Speakers) teaching materials which can have implications for language learning for foreign speakers. This study uses a qualitative method with a case study approach. The source of this research data is dialogue in Practical BIPA teaching materials by the Ministry of Education and Culture.Data collection techniques using document techniques. Data analysis techniques in this study used the Spradley model analysis techniques, through 4 stages, namely, domain analysis, taxonomy, componential, and cultural theme analysis. The findings in this study indicate that there are 5 types of illocutionary speech acts, namely assertive, directive, commissive, expressive, and declarative. These findings can have implications for language learning for foreign speakers, especially BIPA learning. Understanding illocutionary speech acts can help foreign speakers to develop communicative abilities of foreign speakers. Insight into knowledge of illocutionary speech acts can help foreign speakers understand cultural norms related to the use of the target language. Speech act studies can also improve the ability to understand and use language in appropriate social contexts. Insight into illocutionary speech acts also helps foreign speakers to be more careful of errors or misunderstandings in communication. Can be used as material for foreign speakers in negotiating, convincing, and influencing others when communicating.